Morbidity Pattern among Under Five Children in a Selected Upazilla Health Complex - Begum, Masuma; Elham, Nazia; Riya, Sayeda; Shoeb, Nusrat; Rahman, Fatema; Nasreen, Ayesha (Bangladesh Medical Journal, 2021)
A descriptive type of cross sectional study was conducted to find out the morbidity pattern of under five children from February to March 2018. Sick child up to 5 years of age attending Sonarganon Upazila Health Complex, Narayangonj were included in this study. Total 250 respondents were selected by purposive sampling method. Data were collected through structured questionnaire by face to face interview and anthropometric measurement by cheklist. Out of 250 respondents, maximum mother 96(38.4%) were in the age group 20-24 year, only 10 (4%) were above 40 years of age. Most of the respondents (94%) were Muslims, one third of them (34%) had non formal education and nearly one third (32%) had completed primary education. About three forth of the respondents (73.6%) were house wives and 40% live in kacha houses. Monthly family incomes 12000TK of the (36.8%) respondent and more than (67%) two third had sanitary latrine. Majority of the children (59.6%) were within the age group of 12 months or less and mean age + SD was 15 + 12.8 months and majority were female child (51.2%). Mean weight + SD and mean height + SD of the children were 7.84 + 2.76 kg and 67.77 cm + 13.5 cm respectively. Among the morbidity it was found that 26.4% were ARI followed by diarrhoea 18.8%, fever 18% pneumonia 13.6%, skin diseases 6.8%, helminthiasis 6.4%, anemia 4.8%, mumps 3.6% and malnutrition 1.6%. Majority of the children (60%) completed immunization. Diarrhoea was found more common among illiterate and non-formal educated mothers (55.58%). Acute respiratory infection (ARI) was more prevalent in children who lived in kacha house. Pneumonia was more common among the children of business women (33.3%). This study reveals the existing morbidity pattern of under 5 children and would be helpful for development of health services of under 5 children. Bangladesh Med J. 2021 January; 50(1) : 33-38